2021
DOI: 10.1097/pai.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-18 Immunohistochemical Staining Facilitates the Identification of Metastatic Carcinoma of Gastric or Pancreatic Origin in Effusion Specimens

Abstract: Determining the primary origin of a malignant effusion remains a common challenge for cytopathologists. Although immunohistochemical (IHC) markers are available for most primary sites, ideal IHC markers for metastatic gastric adenocarcinoma and pancreatic ductal adenocarcinoma are lacking, and related interpretation is often hindered by mesothelial cells. We recently revealed that claudin-18 IHC staining is useful for identifying the stomach and pancreas as the primary sites of metastatic adenocarcinoma. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study by Yang et al. ( 29 ) revealed that claudin-18 is a sensitive and specific marker for adenocarcinomas arising from the gastric and pancreaticobiliary ducts, boasting a sensitivity of 79% and a specificity of 93%. However, claudin-18 positivity was also noted in over half (more than 54%) of MOC cases, indicating that while useful, claudin-18 expression alone cannot definitively distinguish MOC from tumors of pancreaticobiliary duct origin.…”
Section: Moc Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…The study by Yang et al. ( 29 ) revealed that claudin-18 is a sensitive and specific marker for adenocarcinomas arising from the gastric and pancreaticobiliary ducts, boasting a sensitivity of 79% and a specificity of 93%. However, claudin-18 positivity was also noted in over half (more than 54%) of MOC cases, indicating that while useful, claudin-18 expression alone cannot definitively distinguish MOC from tumors of pancreaticobiliary duct origin.…”
Section: Moc Diagnosis and Differential Diagnosismentioning
confidence: 99%